Pengaruh Terapi Bermain Walkie Talkie TerhadapTingkat Kecemasan Akibat Hospitalisasi Pada Anak UsiaPrasekolah Di Rsud Dr. Moewardi - Aini, Arrum Putri; , Endang Zulaicha S, S. Kp., M. (2016)
Hospitalization causes children separate from family, must adapt to the new environment, body pain due to injury, and autonomy reduced. This makes a child will feel fear, feel threatened, quiet, agitated, and anxious. Children who had anxiety can be overcome by nursing interventions, one method that can be used by play therapy. One of media to play using the environment facility is walkie talkie or phone cans. This research aimed to determine the effect of walkie talkie play therapy towards anxiety level due to the hospitalization on pre school children at RSUD Dr. Moewardi. The research used one group pretest posttest design. This research used the intervention group without a control group. Intervention used with walkie talkie play therapy. Population the research were pediatric patients treated at children medical room Melati II RSUD Dr. Moewardi Surakarta in the two months in 2015, on October and November amount 315 children. The research sample as many 32 children by used technique sampling purposive sampling or judgment sample. Anxiety instument in this research used T - MAS ( Taylor Manifest Anxiety Scale) who modification by Wibowo (2011). The tools used for walkie talkie media play therapy consists of tin cans, nylon, glue, paper scissors, markers, paper, matchsticks. Data analyses used paired t-test. Before the walkie talkie play therapy done to children's anxiety level mostly with moderate anxiety level. After walkie talkie therapy play children's anxiety levels mostly with mild anxiety level. Conclusions of research there was statically a significant effect of walkie talkie play therapy towards anxiety level due to the hospitalization on preschool children at RSUD Dr. Moewardi (p < 0,05).